Case Report: Phosphaturic mesenchymal tumor presenting solely as knee pain without hypophosphatemia - Cao, Qianqian; Cheng, Cheng; Dai, Zhipeng (Frontiers in Oncology, 2025)
Phosphaturic mesenchymal tumor (PMT) is a rare tumor disease that often leads to tumor-induced osteomalacia (TIO). The typical manifestations of this disease include hypophosphatemia and osteomalacia. The main symptom in most PMT patients is diffuse pain throughout the body. However, we report a PMT patient with typical histological features but without hypophosphatemia and TIO. This patient only presented with pain in the right knee joint. At 6 months and 1 year after surgery, follow-up revealed that the patient’s swelling and pain in the right knee joint had disappeared. Moreover, the imaging and biochemical examinations conducted at the local hospital showed normal results.